Streptomyces sp. MUM256: A Source for Apoptosis Inducing and Cell Cycle-Arresting Bioactive Compounds against Colon Cancer Cells - Tan, Loh Teng Hern; Chan, Chim Kei; Chan, Kok Gan; Pusparajah, Priyia; Khan, Tahir Mehmood; Ser, Hooi Leng; Lee, Learn Han; Goh, Bey Hing (MDPI, 2019)
New and effective anticancer compounds are much needed as the incidence of cancer continues to rise. Microorganisms from a variety of environments are promising sources of new drugs; Streptomyces sp. MUM256, which was isolated from mangrove soil in Malaysia as part of our ongoing efforts to study mangrove resources, was shown to produce bioactive metabolites with chemopreventive potential. This present study is a continuation of our previous efforts and aimed to investigate the underlying mechanisms of the ethyl acetate fraction of MUM256 crude extract (MUM256 EA) in inhibiting the proliferation of HCT116 cells. Our data showed that MUM256 EA reduced proliferation of HCT116 cells via induction of cell-cycle arrest. Molecular studies revealed that MUM256 EA regulated the expression level of several important cell-cycle regulatory proteins. The results also demonstrated that MUM256 EA induced apoptosis in HCT116 cells mediated through the intrinsic pathway. Gas chromatography-mass spectrometry (GC-MS) analysis detected several chemical compounds present in MUM256 EA, including cyclic dipeptides which previous literature has reported to demonstrate various pharmacological properties. The cyclic dipeptides were further shown to inhibit HCT116 cells while exerting little to no toxicity on normal colon cells in this study. Taken together, the findings of this project highlight the important role of exploring the mangrove microorganisms as a bioresource which hold tremendous promise for the development of chemopreventive drugs against colorectal cancer. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.